2014
DOI: 10.1088/2043-6262/6/1/015012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of graphene oxide particles on viscosity stabilization for diluted polymer solutions using in enhanced oil recovery at HTHP offshore reservoirs

Abstract: Over 60% of the original oil in a place (OOIP) is retained in a reservoir after conventional methods have been exploited. Application of enhanced oil recovery (EOR) technology gives an additional chance to get out possibly about 20% more oil from the reservoir. The use of watersoluble polymers improves the water-oil mobility ratio, therefore, the displacement efficiency increased, and leads to enhanced oil recovery. High-molecular-weight polyacrylamide group is widely and successfully used in EOR. But no comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…This is a phenomenon which is not commonly seen; the increase of concentration generally leads to an increase in viscosity. One explanation for the reduction in polymer viscosity could be that it is due to the presence of radical degeneration from the PG, which happens when produced radicals react with the polymer backbone, resulting in a reduction of molecular weight [ 37 ]. A study into the viscosity of graphene oxide nanoparticles dispersed in water however, did not observe the reduction of viscosity with an increase in graphene concentration [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is a phenomenon which is not commonly seen; the increase of concentration generally leads to an increase in viscosity. One explanation for the reduction in polymer viscosity could be that it is due to the presence of radical degeneration from the PG, which happens when produced radicals react with the polymer backbone, resulting in a reduction of molecular weight [ 37 ]. A study into the viscosity of graphene oxide nanoparticles dispersed in water however, did not observe the reduction of viscosity with an increase in graphene concentration [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the presence of GO provided additional thermal stability of the modified membrane. Increasing in the thermal stability of GOIM-P could be due to GO particles and the functional groups on GO that play the role as a reducing and sacrificed agent that lead to slow down or limit the degradation process [ 51 ]. The result is in line with what we have reported previously [ 32 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…in enhancing the mechanical properties of chemically crosslinked poly(acrylic acid) . In advanced drilling fluid, GO is also used as an additive for fluid‐loss control, as a viscosity modifier for EOR or as a crude oil/water emulsion systems stabilizer. Although previous research proclaimed the use of GO as a reinforcing nanofiller of PAM, but PAM itself has less tolerance to high salinity and high temperature (HSHT) compared to the HPAM.…”
Section: Introductionmentioning
confidence: 99%